Strawberries Added to the Usual Diet Suppress Fasting Plasma Paraoxonase Activity and Have a Weak Transient Decreasing Effect on Cholesterol Levels in Healthy Nonobese Subjects. (3rd July 2016) - Zasowska-Nowak, Anna; Nowak, Piotr J.; Bialasiewicz, Piotr; Prymont-Przyminska, Anna; Zwolinska, Anna; Sarniak, Agata; Wlodarczyk, Anna; Markowski, Jaroslaw; Rutkowski, Krzysztof P.; Nowak, Dariusz
Abstract : Objective: Strawberries can improve oxidants–antioxidants balance and reduce some cardiovascular risk factors in obese subjects. Paraoxonase-1 (PON-1) is a high-density lipoprotein–associated enzyme with antioxidant properties that can protect from coronary artery disease in humans. We examined the effect of strawberry consumption on plasma PON-1 activity and lipid profile in healthy nonobese subjects. Methods: Thirty-one subjects (body mass index [BMI] 24.4 ± 4.0 kg/m 2 ) on their usual diet consumed 500 g of strawberry pulp daily for 30 days (first course) and after a 10-day washout the cycle was repeated (second course). Fasting blood and spot morning urine samples were collected before, during, and after each strawberry course (8 time points) for determination of paraoxonase and arylesterase PON-1 activities and lipid profile. Twenty subjects served as controls with respect to cholesterol and PON-1 activities changes over the study period. Results: Strawberries decreased mean plasma paraoxonase PON-1 activity and this effect was more evident after the second course (by 11.6%, p < 0.05) than after the first course (5.4%, p = 0.06), whereas arylesterase activity was constant. Strawberries altered total cholesterol levels ( p < 0.05) with a tendency to transiently decrease it (by 5.1%) only after 15 days of the first course. Triglycerides and high- and low-density lipoprotein cholesterol did not change in response to fruit consumption. No changes in PON-1 activities and lipid profile were noted in controls. Paraoxonase correlated with arylesterase activity (ƿ from 0.33 to 0.46 at the first 7 time points, p < 0.05). This association disappeared at the end of study (ƿ = 0.07) when the strongest inhibition of paraoxonase was noted. Conclusions: Supplementation of the usual diet with strawberries decreased paraoxonase PON-1 activity and did not improve lipid profiles in healthy nonobese subjects. Further studies are necessary to establish the clinical significance of paraoxonase suppression and to define a group of healthy subjects who can benefit from strawberry consumption with respect to cholesterol levels.